2021
DOI: 10.1002/bit.27670
|View full text |Cite
|
Sign up to set email alerts
|

Pilot‐scale demonstration of an end‐to‐end integrated and continuous biomanufacturing process

Abstract: There has been increasing momentum recently in the biopharmaceutical industry to transition from traditional batch processes to next‐generation integrated and continuous biomanufacturing. This transition from batch to continuous is expected to offer several advantages which, taken together, could significantly improve access to biologics drugs for patients. Despite this recent momentum, there has not been a commercial implementation of a continuous bioprocess reported in the literature. In this study, we descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 21 publications
0
45
0
Order By: Relevance
“…The high pressure to reduce production costs drives innovation towards new approaches such as intensified fed‐batches (Chen et al, 2018; Jordan et al, 2018; Xu et al, 2020; W. C. Yang et al, 2016), perfusion cultures and/or continuous production (J.‐M. Bielser et al, 2018; Coolbaugh et al, 2021; Daniel Johannes Karst et al, 2018; Warikoo et al, 2012; Wolf et al, 2020). The highest volumetric productivity per reactor volume is promised by perfusion processes, while the low residence time of the protein in the reactor can be beneficial for some quality attributes (J. M. Bielser et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The high pressure to reduce production costs drives innovation towards new approaches such as intensified fed‐batches (Chen et al, 2018; Jordan et al, 2018; Xu et al, 2020; W. C. Yang et al, 2016), perfusion cultures and/or continuous production (J.‐M. Bielser et al, 2018; Coolbaugh et al, 2021; Daniel Johannes Karst et al, 2018; Warikoo et al, 2012; Wolf et al, 2020). The highest volumetric productivity per reactor volume is promised by perfusion processes, while the low residence time of the protein in the reactor can be beneficial for some quality attributes (J. M. Bielser et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…While design variables have been explored quite extensively in past work in continuous viral inactivation (Amarikwa et al, 2019; Coolbaugh et al, 2021; Gillespie et al, 2019; Klutz et al, 2016; Orozco et al, 2017; Parker et al, 2018), disturbance rejection has not been discussed directly. Disturbance rejection is especially important to consider when operating continuously for an extended period of time.…”
Section: Resultsmentioning
confidence: 99%
“…work in continuous viral inactivation (Amarikwa et al, 2019;Coolbaugh et al, 2021;Gillespie et al, 2019;Klutz et al, 2016;Orozco et al, 2017;Parker et al, 2018), disturbance rejection has not been discussed directly.…”
Section: While Design Variables Have Been Explored Quite Extensively ...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, Godawat et al ( 2015 ) were able to combine a perfusion bioreactor with two periodic PCC units for initial capture and successive ion‐exchange steps, showing it is feasible to fully create and integrate an end‐to‐end continuous bioprocessing platform. More recently, Coolbaugh et al ( 2021 ) have demonstrated such end‐to‐end continuous processes are scalable by showing a successful proof‐of‐concept at pilot‐scale.…”
Section: Current Needs In the Integrated Continuous Bioprocessingmentioning
confidence: 99%